Pure tone audiograms and possible aminoglycoside-induced hearing loss in belugas ( Delphinapterus leucas ) - Finneran, James J.; Carder, Donald A.; Dear, Randall; Belting, Traci; McBain, Jim; Dalton, Les; Ridgway, Sam H. (The Journal of the Acoustical Society of America, 2005)
A behavioral response paradigm was used to measure pure-tone hearing sensitivities in two belugas (Delphinapterus leucas). Tests were conducted over a 20-month period at the Point Defiance Zoo and Aquarium, in Tacoma, WA. Subjects were two males, aged 8–10 and 9–11 during the course of the study. Subjects were born in an oceanarium and had been housed together for all of their lives. Hearing thresholds were measured using a modified up/down staircase procedure and acoustic response paradigm where subjects were trained to produce audible responses to test tones and to remain quiet otherwise. Test frequencies ranged from approximately 2 to 130 kHz. Best sensitivities ranged from approximately 40 to 50 dB re 1 μPa at 50–80 kHz and 30–35 kHz for the two subjects. Although both subjects possessed traditional “U-shaped” mammalian audiograms, one subject exhibited significant high-frequency hearing loss above 37 kHz compared to previously published data for belugas. Hearing loss in this subject was estimated to approach 90 dB for frequencies above 50 kHz. Similar ages, ancestry, and environmental conditions between subjects, but a history of ototoxic drug administration in only one subject, suggest that the observed hearing loss was a result of the aminoglycoside antibiotic amikacin.